Accounting for the effect of health on economic growth - David N. Weil (Brown University, Department of Economics, 2005)
I use microeconomic estimates of the effect of health on individual outcomes to construct macroeconomic estimates of the proximate effect of health on GDP per capita. I employ a variety of methods to construct estimates of the return to health, which I combine with crosscountry and historical data on height, adult survival rates, and age at menarche. Using my preferred estimate, eliminating health differences among countries would reduce the variance of log GDP per worker by 9.9 percent, and reduce the ratio of GDP per worker at the 90th percentile to GDP per worker at the 10th percentile from 20.5 to 17.9. While this effect is economically significant, it is also substantially smaller than estimates of the effect of health on economic growth that are derived from cross-country regressions.
Keywords: 330; Gesundheit; Sozialprodukt; Schätzung; Welt; Makroökonomischer Einfluss